Plant Defense Mechanisms 2022
DOI: 10.5772/intechopen.101513
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress and Plant Molecular Responses

Abstract: Plants being sessile suffer from several abiotic stresses during growth. These include drought, salinity, heavy metal, temperature, and nutrient stress. Salt stress is one of the devastating abiotic stresses that plant suffers under natural growth conditions. It is more common in arid regions due to excessive evaporation, which causes the accumulation of inorganic salts disrupting the plant metabolism. It also triggers the influence of drought stress, as plants are unable to absorb water. Additionally, it also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Salinization negatively affects plant biochemical and physiological processes such as photosynthesis, stomatal activity, neutralization of reactive oxygen species, enzyme activity, and plant height and weight (Tavakkoli et al, 2010;Khudyaev and Banaev, 2012;Ivanishchev, 2019;Yin et al, 2021). Salt stress in plants suppresses the formation of proteins and increases the breakdown of already formed protein complexes (Vargas et al, 2017;Ivanishchev, 2019;Chaudhry et al, 2022). A decrease in protein synthesis shows itself in a noticeable decrease in growth and development rates of plants and disruption of metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinization negatively affects plant biochemical and physiological processes such as photosynthesis, stomatal activity, neutralization of reactive oxygen species, enzyme activity, and plant height and weight (Tavakkoli et al, 2010;Khudyaev and Banaev, 2012;Ivanishchev, 2019;Yin et al, 2021). Salt stress in plants suppresses the formation of proteins and increases the breakdown of already formed protein complexes (Vargas et al, 2017;Ivanishchev, 2019;Chaudhry et al, 2022). A decrease in protein synthesis shows itself in a noticeable decrease in growth and development rates of plants and disruption of metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in protein synthesis shows itself in a noticeable decrease in growth and development rates of plants and disruption of metabolic processes. An increase in the degree of salinity leads to disruption of homeostatic water balance (Ivanishchev, 2019;Chaudhry et al, 2022). Numerous studies have shown that toxicity occurs at lower concentrations in the case of chloride salinity than in the case of sulfate salinity (Khudyaev and Banaev, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Plants often experience unfavorable environmental conditions in growing habitats. Depending on the stress response, plants can retain information for a time after a previous stress (known as stress memory), so they can adapt more quickly to the same adversity in the future [19]. Epigenetic regulation is closely associated with the development of stress memories [19][20][21].…”
Section: Epigenetic Memory and Chromatin Dynamics In Plant Stress Res...mentioning
confidence: 99%
“…Depending on the stress response, plants can retain information for a time after a previous stress (known as stress memory), so they can adapt more quickly to the same adversity in the future [19]. Epigenetic regulation is closely associated with the development of stress memories [19][20][21]. Research showed that stress treatment can alter the chromatin status of genes that respond to stress, and these changes persist after recovery and even in progeny [22][23][24].…”
Section: Epigenetic Memory and Chromatin Dynamics In Plant Stress Res...mentioning
confidence: 99%